Pengembangan Video Praktikum Bermuatan Chemo-Entrepreneurship (CEP) untuk Meningkatkan Pemahaman Materi Sifat Koligatif Larutan Peserta didik SMA - Agus Kamaludin; Aqilatun Ni'mah (Jurnal Penelitian Pendidikan IPA, 2023)
In the era of the industrial revolution 4.0, soft skill development practicum, entrepreneurship, and mastery of material concepts are all critical components in meeting challenges. By incorporating entrepreneurial aspects into practicum, efforts can be made to improve its quality. This research aims to create a practical video with Chemo-entrepreneurship (CEP) on the colligative properties of solutions and evaluate the video quality and student reactions to the product. This study uses a 4D development model to conduct development research (R&D) (Define, Design, Develop, and Disseminate). The product is a chemo-entrepreneurship practicum video in an mp4 that shows making ice cream, soursop syrup, and salted eggs. One material expert lecturer, one media expert lecturer, and four reviewers validate the product. The results of media experts' product quality assessment receive a 95 percent rating in the Very Good category, material experts receive a 90 percent rating in the Very Good category, and senior high school chemistry teachers receive a 95 percent rating in the Very Good category. With a positive response rate of 97 percent, the students were enthusiastic about the video. Based on the evaluation results, it can be concluded that the developed product is suitable for use in the learning process in senior high school on the collaborative properties of solutions to improve entrepreneurship skills and students' understanding